PENDIDIKAN EKONOMI BERKELANJUTAN DIDESA HILIONAHA: MEWUJUDKAN KEUANGAN PRIBADI MASYARAKAT YANG SEHAT DI TENGAH KRISIS - Laia, Baziduhu; Anita Zagoto (Haga : Jurnal Pengabdian Kepada Masyarakat, 2024)
Global economic crises and financial uncertainties often affect the welfare of society, particularly in terms of personal financial management. Therefore, it is essential to enhance financial literacy among communities so they can manage financial resources wisely and survive during times of crisis. This community service program aims to provide economic education to the people of Hilionaha Village regarding healthy and sustainable personal financial management. The methods used include community-based training, workshops, individual coaching, and group discussions, all aimed at developing understanding and skills in household budgeting, savings planning, and basic investment strategies. The results of this activity show a significant increase in the community's understanding of how to manage their finances, as well as their ability to create realistic budgets and prioritize spending. However, challenges such as limited access to financial institutions and restricted income remain barriers. Overall, this community service activity has had a positive impact on personal financial management at the household level and is expected to strengthen the economic resilience of the people of Hilionaha Village in facing financial challenges